KAJIAN MANAJEMEN OPTIMALISASI PENERANGAN JALAN UMUM KOTA SEMARANG - Widodo, Aris (Universitas Negeri Semarang, 2016)
This research mainly aims to give input to Semarang Local Government in the efficiency of electricity utilization to the street illumination and the management of income tax from the societies, so they can be utilized optimally, directly, and in integrated way in order to the management of city infrastructures service. This research using the influence of traffic passenger car unit (pcu) for optimizing in a low density of traffic condition. The data of the Average Daily Traffic (ADT) volume on Pahlawan street was gathered from 6.00 p.m-6.00 a.m in every 15 minutes. The data was analyzed using quartile technique with K1 (25%) and K2 (50 %), then the researcher designed a line chart table of a link between the ADT and the time of the electricity switching on. In working days, the results are (1) the efficient time of street illumination in K1 (25%) was between 10.30 p.m-3.45 a.m, (2) in K2 (50%) was between 9.45 p.m-4.30 a.m. Due to the security and the beauty of the town and also considering the density of the traffic, the optimization and the dimming of the electricity are not needed in holidays. The optimization using ballast dimming (40%) from 250 watt to 150 watt for all lamps, obtained a significant account 32,4 Lx for average illumination. It is still fulfill the minimal requirement of 7 Lx for the average illumination on the collector street type. The optimization with dimming system obtained an efficiency in K1 (25%) was 23.16% and in K2 (50%) was 25,05%. Kajian ini bertujuan untuk memberi masukan kepada Pemerintah Kota Semarang dalam rangka efisiensi penggunaan daya listrik untuk penerangan jalan umum dan pengelolaan pendapatan pajak dari masyarakat. Kajian ini menggunakan pengaruh dari kepadatan lalu lintas jalan dalam satuan mobil penumpang (smp), guna optimalisasi penerangan jalan umum dalam kondisi kepadatan lalu lintas jalan yang rendah. Data Volume Lalu lintas Harian Rata-rata (LHR) Jalan pahlawan dilakukan dari jam 18.00 sore hari, hingga 06.00 WIB pagi dengan pencatatan per 15 menit, kemudian dibuat tabel grafik garis hubungan antara LHR dengan waktu penyalaan lampu penerangan jalan umum Kota Semarang, pada hari kerja diperoleh : (1) waktu efisiensi penyalaan lampu pada K1 (25%) antara jam 22.30 sampai dengan 03.45 Wib, (2) waktu efisiensi penyalaan lampu pada K2 (50%) antara jam 21.45 sampai dengan 04.30 Wib. Sedangkan pada hari libur berdasarkan keamanan dan keindahan kota serta volume lalulintas kendaraan yang cukup padat maka tidak ada perlakuan optimalisasi peredupan. Optimalisasi dengan sistem peredupan ballast (40%) dari daya 250 watt menjadi 150 watt pada seluruh titik lampu penerangan, didapat perhitungan kuat penerangan rata-rata sebesar 32,4 Lx, dan masih memenuhi syarat minimal kuat penerangan rata-rata untuk jenis jalan kolektor sebesar 7 Lx. Sistem optimalisasi dengan peredupan diperoleh efisiensi pada K1 (25%) sebesar 23,16 % dan K2 (50%) sebesar 25,05%..